Elasto-plastic behavior of thermoplastic matrix plates with rectangular hole - Arslan, N (Technomic Publ Co Inc, 2000)
The elasto-plastic stress analysis of the thermoplastic matrix plates with rectangular hole is carried out by using finite elements. A two-dimensional finite element computer program is developed for elasto-plastic stress analysis. Isoparametric quadratic element with nine nodes is used with Lagrange polynomial as an interpolation function. The spreads of the plastic zones and variations of the residual stresses are obtained in different orientation angles and loads. It is shown that the path around the hole location can be designed to decrease the stress concentrations. The results are presented in diagrams and compared with some of the relevant studies in the literature.
Keywords: elasto-plastic; residual stress; fibrous composite material; finite element method